Size polymorphism and low sequence diversity in the locus encoding the Plasmodium vivax rhoptry neck protein 4 (PvRON4) in Colombian isolates (2016)
Background: Designing a vaccine against Plasmodium vivax has focused on selecting antigens involved in invasion mechanisms that must have domains with low polymorphism for avoiding allele-specific immune responses. The rhoptry neck protein 4 (RON4) forms part of the tight junction, which is essential in the invasion of hepatocytes and/or erythrocytes; however, little is known about this locus’ genetic diversity. Methods: DNA sequences from 73 Colombian clinical isolates from pvron4 gene were analysed for characterizing their genetic diversity; pvron4 haplotype number and distribution, as well as the evolutionary forces determining diversity pattern, were assessed by population genetics and molecular evolutionary approaches. Results: ron4 has low genetic diversity in P. vivax at sequence level; however, a variable amount of tandem repeats at the N-terminal region leads to extensive size polymorphism. This region seems to be exposed to the immune system. The central region has a putative esterase/lipase domain which, like the protein’s C-terminal fragment, is highly conserved at intra- and inter-species level. Both regions are under purifying selection. Conclusions: pvron4 is the locus having the lowest genetic diversity described to date for P. vivax. The repeat regions in the N-terminal region could be associated with immune evasion mechanisms while the central region and the C-terminal region seem to be under functional or structural constraint. Bearing such results in mind, the PvRON4 central and/or C-terminal portions represent promising candidates when designing a subunit-based vaccine as they are aimed at avoiding an allele-specific immune response, which might limit vaccine efficacy. © 2016 The Author(s).